A case of blistering distal dactylitis due to Methicillin-resistant Staphylococcus aureus - Ghouri, Raza Gulzar; Ahmed, Raja Mobeen; Asad, Amna; Saeed, Wajieha; Mansoor, Mahym (Journal of Pakistan Association of Dermatologists, 2020)
Blistering distal dactylitis is a distinct entity presenting with localized group A Î²-hemolytic Streptococcus infection of the distal phalanx usually in a child manifesting as multiple bullae on hands and feet. A case of BDD caused by Methicillin-resistant Staphylococcus aureus (MRSA) in a 12-year-old male is reported. There was no trauma and other differentials of BDD were ruled out. Patient responded to medication and was discharged. This is the first reported case of BDD in the local setting. We recommend that it should be considered in the differential diagnoses of acral blister formation especially in children. Â 